RESPONSE OF SEEDLINGS OF TWO GRAPE CULTIVARS TO DIFFERENT LEVELS OF NITROGEN FERTILIZERS - Nagham Salah Salim (European Journal of Agricultural and Rural Education, 2022)
This experiment was carried out in the nursery of the Department of Horticulture and Landscaping at the College of Agriculture and Forestry / University of Mosul / Iraq during the 2020 growing season to study the effect of different levels of nitrogen fertilization, on the growth of seedlings of two grape cultivars. In the implementation of the experiment, a split-R.C.B.D was followed for the factorial experiments with two factors, where four concentrations of nitrogen (0, 1.5, 3.0, and 4.5) Nitrogen mg. seedlings -1 seedling using urea as a source of nitrogen (46%N). Two grape cultivars were used, are Des Al-Anz and Jafka 4X2 to become 8 treated with three replications and with (5) seedlings in the experimental unit per replicate. The results showed significant superiority of urea fertilizer in the characteristics (height of the main stem (cm), main stem diameter (cm), leaves number, area of one leaves (cm2). The cultivar Des Ans showed significant superiority in the studied parameter main stem diameter (cm), and JAFKA cultivar was significant superiority in area of one leaves (cm2).